A Study of Infertility Cases in Males in Basrah Province - Edan, Hussein Alaa; Dawood Salman Mahdi; Ihsan Edan Alsaimary (University of Thi-Qar Journal of Science, 2023)
Infertility remains a global health challenge with devastating psycho-social consequences in many communities, and the underlying long-term risk of couple separation is also a major clinical and social problem. Infertility is defined as the inability of a couple to conceive naturally after one year of intercourse. A case-control study was carried out among males who have infertility and who attended the Infertility and in vitro fertilization Center of Basrah province in the period extended from September 2021 to June 2022. A questionnaire was used to record The special notes. Seminal fluid samples were collected from (176 patients and controls were divided into 88 patients of male samples and 88 samples of the control group). In the present study, age was divided into three groups, which were statistically non-significant. The residence was also non-significant, which included central and peripheral areas. The results also showed no statistical significance between smokers and nonsmokers. The laboratory results showed that the analyzed seminal fluid parameters such as volume, sperm count, grade A, grade D, and Morphology of sperm in the patient’s group differed significantly from that of the control group (P. value <0.05). Compared to primary infertility (N=61,34.6%) or secondary infertility (N=27,15.4%), the analyzed seminal fluid parameters showed no statistical significance. In addition, the seminal fluid abnormalities, which were divided into six groups, that were found significantly statistically significant in patients from controls, include asthenozoospermia, necrozoospermia, teratozoospermia, and leukocytopenia. (P. value <0.05).